A Stackelberg game based content caching algorithm in energy-harvesting small cell networks - Xueting WANG; Qi ZHU; Han HU (Dianxin kexue)
To improve the users' satisfaction of download files, a caching based resource allocation algorithm in energy-harvesting small cell networks was proposed, which was established as a Stackelberg game that jointly optimized user accessing and small cells' content updating. Firstly, a coalitonal game for users to transfer between coalitions (small cells) with user satisfaction being utility function was proposed, and the transition was accepted once the utility of user after transferring satisfies the transition rules. Several users were allowed to be served by a same cell, and users accessing the same small cell would share the same channel using NOMA. Then, to maximize the benefit, a cache updating scheme was put forward to update the files cached by small cells. The equilibrium solution could be achieved after finite iterations of the two algorithms. The simulation results show that the proposed novel algorithm performs better in user satisfaction and energy-saving comparing with algorithm using principle of proximity.